“How Incredibly Awesome!” — Click Here to Read More - Ahn, Hyung-il; Geyer, Werner; Dugan, Casey; Millen, David (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
We investigate the impact of a discussion snippet's overall sentiment on a user's willingness to read more of a discussion. Using sentiment analysis, we constructed positive, neutral, and negative discussion snippets using the discussion topic and a sample comment from discussions taking place around content on an enterprise social networking site. We computed personalized snippet recommendations for a subset of users and conducted a survey to test how these recommendations were perceived. Our experimental results show that snippets with high sentiments are better discussion "teasers."